PERAN KEPERCAYAAN DALAM TRANSAKSI JURNAL BELI BERAS CV.RAHMA 35 KABUPATEN SIDENRENG RAPPANG - Padapi, Astrini; Nursyamsih; Aulia, Dhiva; Alif, Muh. Qisand (LP2M Universitas Jember, 2025)
Premium rice “PB Rahma 35,” which is processed hygienically and in accordance with Islamic business principles, is the flagship product of CV. Rahma 35, a rice milling company located in Sidrap, South Sulawesi. However, the company's dependence on a single supplier, intense competition, and lack of transaction transparency make it difficult to gain the trust of suppliers and customers. This study recommends methods to enhance production, digital marketing, and direct sales while identifying supply chain management issues such as communication with suppliers and product quality perception. Interview results indicate that timely payments and support services like transportation and fertilizer assistance are crucial for building partner trust. These findings assist CV. Rahma 35 in improving its competitiveness and business procedures. The objectives of this community service activity are: to improve communication and transparency between CV. Rahma 35 and its business partners, use guidance and training to strengthen fair and sustainable partnership structures, and establish a feedback system to evaluate and enhance partner trust. Conducted from March to May 2025, the CV. Rahma 35 Management Team actively participated in: Program planning through FGD (Focus Group Discussion) and evaluating the results of the community service program together with the team. Through strategic efforts such as conducting focused group discussions (FGD), strengthening the partnership system, and providing complaint services via WhatsApp, CV Rahma's community service program has successfully increased client trust.